2021
DOI: 10.1200/jco.20.00475
|View full text |Cite
|
Sign up to set email alerts
|

Immune Biology of Acute Myeloid Leukemia: Implications for Immunotherapy

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 142 publications
(243 reference statements)
0
47
0
Order By: Relevance
“…The last 3-5 years have seen significant progress made in the understanding of the immune biology of AML [84] and advances in technology resulting in the development of novel AML-directed T-cell therapeutic approaches. Despite the numerous ongoing trials, we believe that T-cell immunotherapies for myeloid malignancies are still in their infancy.…”
Section: Discussionmentioning
confidence: 99%
“…The last 3-5 years have seen significant progress made in the understanding of the immune biology of AML [84] and advances in technology resulting in the development of novel AML-directed T-cell therapeutic approaches. Despite the numerous ongoing trials, we believe that T-cell immunotherapies for myeloid malignancies are still in their infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, older patients with high HCT comorbidity Index (HCT-CI) 24 scores, would be conditioned with RIC regimens, which, in turn, are associated with a higher probability of relapse, particularly if MRD is present. 25,26 It might be preferable, therefore to treat those patients on novel investigational protocols, for example using cellular therapy modalities that are under development, [27][28][29] or new chemotherapy regimens 30 such as venetoclax plus HMA, rather than proceeding to HCT using current transplant strategies. In fact, Del Galy et al 31 observed comparable 2-and 3-year overall survival with HCT and non-HCT therapy among 174 consecutive patients 60-74 years of age.…”
Section: Impact Of Cytogeneticsmentioning
confidence: 99%
“…In recent years, different treatment platforms have overall been developed to harness anti-neoplastic T-cell activity in individuals affected with cancer, including hematologic malignancies: (a) recruitment of T cells independently of TCR specificity through T-cellengaging antibody constructs, (b) reactivation of endogenous T-cell immune responses through either immune-checkpoint inhibitors (ICPIs) or other immunological strategies, and (c) genetic engineering of T cells, namely TCR-modified and chimeric antigen receptor (CAR) T cells, to be utilized as adoptive immunotherapy [1,[63][64][65]. Relevant to this latter point, van der Lee et al, isolated and sequenced the CLAVEEVSL-specific TCR from one clone that specifically and strongly recognized HLA-A*02:01 peptide-pulsed targets and NPM1-mutated AML blasts [20].…”
Section: Exploiting Genetic Engineering Of T Cells Against Npm1-mutated Aml Cellsmentioning
confidence: 99%
“…However, single-agent ICPIs have so far demonstrated very modest anti-leukemic activity in clinical trials for relapsed/refractory AML patients, maybe due to suboptimal patient selection and lower mutational load of AML compared to solid tumors [1,68]. The role of several combination approaches of ICPIs with either hypomethylating agents (HMAs) or more intensive cytotoxic chemotherapy has recently been evaluated and is still under investigation in clinical trials enrolling AML patients at different disease stages, as comprehensively reviewed elsewhere [1,[63][64][65]69]. Interestingly, Greiner et al, recently performed flow-cytometry and microarray analyses on a total of 30 AML samples, including 15 cases with NPM1 mutations, to assess PD-L1 expression in leukemic cells at diagnosis [17,70].…”
Section: Immune-checkpoint Inhibitors and Novel Therapeutic Approaches In Npm1-mutated Amlmentioning
confidence: 99%